THE EFFECT OF INVESTMENT ON ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX AND COMMUNITY WELFARE (CASE STUDY IN BEKASI REGENCY) - Hugo Aries Suprapto; Sumaryoto Sumaryoto; Sugiyanto Saleh (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Inequality in economic growth was widening, when the beginning of March 2020 in Indonesia and various other countries experienced the impact and experienced widespread transmission of the COVID-19 pandemic. The purpose of this study was to analyze the effect of investment on economic growth in Bekasi Regency, the effect of investment on the human development index, the effect of economic growth on the human development index, the effect of economic growth on people's welfare and the influence of the human development index on welfare in Bekasi Regency. This research method useD quantitative methods. If we look at this type of research, it included explanatory research, namely research that explained the causal relationship between variables in hypothesis testing. The data used was secondary data obtained from BPS from 2015 to 2019 (for 5 years), data in the form of time series in Bekasi Regency, West Java. The results showed that investment (X1) had a significant effect on economic growth (Y1). Likewise for the human growth index (HDI), investment had a significant effect on the HDI (Y2). Meanwhile, the variable economic growth had no significant effect on HDI, while economic growth (Y1) had a significant effect on welfare (Y3). Economic growth (Y1) had a significant effect on welfare (Y3)